Effect of serum 25-hydroxyvitamin D level on quadriceps strength: a systematic review and meta-analysis - Michael Tim-yun Ong; Kitson Chun-Kit Tsang; Victor Yan Zhe Lu; Stacy Lok Sze Yam; Wei Shen; Gene Chi-Wai Man; Patrick Shu-hang Yung (BMC, 2024)
Abstract Background Vitamin D deficiency has been linked to poor muscle function, cartilage degeneration, and the development of knee osteoarthritis. However, the impact of serum 25-hydroxyvitamin D [25(OH)D] level on quadriceps muscle strength remains inconclusive, largely due to variations in study designs, differences in study populations, and the influence of confounding factors such as co-supplementation with other vitamins. The existing literature presents mixed findings, highlighting the need for a comprehensive evaluation of the available evidence. Purpose This systematic review and meta-analysis aim to summarise. Study design Systematic review; Level of evidence, 4. Methods Searches were conducted using Medline (Ovid), Embase (Ovid), CINAHL (EBSCOhost), and SPORTDiscus (EBSCOhost), which aimed to summarise recent (published after 2000 and before March 1st, 2024) studies reporting the effects of serum 25(OH)D levels on quadriceps strength. Appraisal tool for Cross-Sectional Studies (AXIS) for cross-sectional studies and Quality in Prognosis Studies (QUIPS) for longitudinal studies. Results from the AXIS and QUIPS tools were used for GRADE quality assessment. The review was carried out using PRIMSA guidelines and registered in PROSPERO (ID: CRD42022313240). Results Four hundred studies were screened and 28 studies with 5752 participants were included. 28 published studies (24 cross-sectional and 4 longitudinal) were identified. Key results supported the significant positive correlation between serum 25(OH)D levels and isokinetic quadriceps strength at 180°/s in elderly and athletic populations with a correlation coefficient of 0.245 (95%CI: 0.078-0.398, p = 0.004). However, no significant correlation was found with isometric quadriceps strength or isokinetic strength at 60°/s (r = 0.190, p = 0.085). There was only a weak negative correlation with MVC. Conclusion This review found a statistically significant positive correlation between serum 25(OH)D levels and isokinetic quadriceps strength. This has important clinical implications, especially in the elderly cohort, with higher 25(OH)D levels being associated with a reduced incidence of falls and fragility fractures.